• NCERT Chapter
Question 5

# Check whether the relation R in R defined as R = {(a, b): a ≤ b3} is reflexive, symmetric or transitive.

R = {(a, b): a b3}

It is observed that

\begin{align} \left(\frac{1}{2},\frac{1}{2}\right) ∉ R , as  \frac{1}{2}>\left(\frac{1}{2}\right)^3 = \frac{1}{8}\end{align}

∴ R is not reflexive.

Now,

(1, 2) ∈ R (as 1 < 23 = 8)

But,

(2, 1) ∉ R (as 23 > 1)

∴ R is not symmetric.

We have

\begin{align} \left(3,\frac{3}{2}\right),\left(\frac{3}{2},\frac{6}{5}\right) ∉ R , as  3>\left(\frac{3}{2}\right)^3 and \frac{3}{2}<\left(\frac{6}{5}\right)^3 \end{align}

But

\begin{align} \left(3,\frac{6}{5}\right) ∉ R , as  3>\left(\frac{6}{5}\right)^3 \end{align}

∴ R is not transitive.

Hence, R is neither reflexive, nor symmetric, nor transitive.

">

Let A = R – {3} and B = R – {1}. Consider the function  f : A → B defined by

• Q:- Show that the relation R in the set A = {1, 2, 3, 4, 5} given by R = { (a,b) ; |a - b| is even}, is an equivalence relation. Show that all the elements of {1, 3, 5} are related to each other and all the elements of {2, 4} are related to each other. But no element of {1, 3, 5} is related to any element of {2, 4}.
• Q:-

Prove that the Greatest Integer Function f : R → R, given by f(x) = [x], is neither one-one nor onto, where [x] denotes the greatest integer less than or equal to x.

• Q:-

Show that the Modulus Function f : R → R, given by f(x) = |x|, is neither oneone nor onto, where | x | is x, if x is positive or 0 and |x| is – x, if x is negative.

• Q:- Show that the relation R in the set R of real numbers, defined as R = {(a, b): a ≤ b2} is neither reflexive nor symmetric nor transitive.
• ## Recently Viewed Questions of Class 12th mathematics

">

Let A = R – {3} and B = R – {1}. Consider the function  f : A → B defined by

• Q:-

If a line has the direction ratios −18, 12, −4, then what are its direction cosines?

• Q:-

Find gof and fog, if

(i) f(x) = | x | and g(x) = | 5x – 2 |
(ii) f(x) = 8x3 and g(x) = x1/3 .

• Q:-

Let f: X → Y be an invertible function. Show that the inverse of f –1 is f, i.e., (f–1)–1 = f.